1994
DOI: 10.1128/aac.38.6.1392
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of artemisinin ether, cycloguanil hydrochloride (alone and in combination with sulfadiazine), quinine sulfate, mefloquine, primaquine phosphate, trifluoperazine hydrochloride, and verapamil on Toxoplasma gondii

Abstract: The in vitro effects of the following antimicrobial agents on Toxoplasma gondii tachyzoites were studied: artemisinin ether (arteether), cycloguanil hydrochloride (cycloguanil), mefloquine, primaquine phosphate, and quinine sulfate, as well as the calcium channel blocker verapamil and the calmodulin inhibitor trifluoperazine hydrochloride. Arteether at .0.5 ,ug/ml and cycloguanil at .1.0 ,ug/ml inhibited T. gondii in vitro. Cycloguanil (2.5 ,ug/ml) combined with a noninhibitory concentration of sulfadiazine (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 22 publications
3
41
1
1
Order By: Relevance
“…At this time supernatants were removed from parallel cultures and stored at Ϫ70°C for measurement of IFN-␥. [ 3 H]Thymidine-pulsed wells were cultured for an additional 12 h, after which they were harvested onto glass-fiber filter strips (Cambridge Technology, Watertown, MA) using an automated PHD cell harvester (Cambridge Technology) and processed as previously described (25). Results are expressed as the mean stimulation index Ϯ SE for each group of animals.…”
Section: T Cell Proliferation Assaymentioning
confidence: 99%
“…At this time supernatants were removed from parallel cultures and stored at Ϫ70°C for measurement of IFN-␥. [ 3 H]Thymidine-pulsed wells were cultured for an additional 12 h, after which they were harvested onto glass-fiber filter strips (Cambridge Technology, Watertown, MA) using an automated PHD cell harvester (Cambridge Technology) and processed as previously described (25). Results are expressed as the mean stimulation index Ϯ SE for each group of animals.…”
Section: T Cell Proliferation Assaymentioning
confidence: 99%
“…Published studies have indicated that the naturally occurring 1,2,4-trioxane artemisinin and artemisinin derivatives such as artemether, originally developed for the treatment of malaria, have the ability to inhibit toxoplasma replication in vitro (2,4,6,10). While these trioxanes have a number of advantages in terms of rapid action and low levels of toxicity, they are limited in terms of absorption, bioavailability, and short half-life (i.e., easy hydrolysis into toxic dihydroartemisinin) (9).…”
mentioning
confidence: 99%
“…We obtained a better inhibition of parasite growth results in vivo with our cyst-forming strain than with the RH strain, but in vitro it was lower than that previously observed by other investigators. 8,15 We believe that the differences observed are due mainly to the strains of T. gondii used, which show differences in sensitivity to various drugs. A recent study showed the selection of mutants of the RH strain of T. gondii resistant to artemisin.…”
Section: Discussionmentioning
confidence: 99%
“…Arteether concentrations Ͼ0.5 g/ml were inhibitory 1 hr after the addition of the drug to the RH strain in in vitro assays with macrophage and enterocyte cultures. 15 In vitro studies performed on fibroblasts infected with the RH strain showed a 100% reduction in parasite growth after treatment with arteether (1 g/ml), a 100% reduction in parasite growth after treatment with artemether (0.1-1 g/ml), and a 98% reduction in parasite growth after treatment with a lower concentration of artemether (0.01 g/ ml). 8 We obtained similar results in this study with our cystic strain.…”
Section: Discussionmentioning
confidence: 99%